Causal associations between gut microbiota and synovitis–tenosynovitis: a two-sample Mendelian randomization study - Yin, Xietian; Zhao, Shichao; Tan, Zhangkui; Xu, Jun; Lu, Qiping (Frontiers in Microbiology, 2024)
Abstract Background: More and more evidence indicated that gut microbiota dysbiosis is related to synovitis and tenosynovitis. Nonetheless, whether these associations are causal is currently unknown. Objectives: A two-sample Mendelian randomization (MR) study was performed to reveal the causality of gut microbiota with synovitis and tenosynovitis. Methods: The summary statistical data from large-scale genome-wide association study (GWAS) was applied as the basis for a two-sample MR analysis. The causal effect was estimated using inverse variance weighted (IVW), weighted median, simple mode, MR Egger, and weighted mode methods, of which IVW was the main method. Meanwhile, the pleiotropy and heterogeneity were detected and measured using MR-Egger regression, Cochran’s Q statistics, funnel plots, and MR pleiotropy residual sum and outlier (MR-PRESSO) methods. Results: The IVW technique demonstrated that genetically predicted five genera including Gordonibacter [odds ratio (OR) = 0.999, 95% confidence interval (CI): (0.9977, 0.9998), p = 0.019], Paraprevotella [OR = 0.999, 95% CI: (0.9971, 0.9999), p = 0.036], Lachnoclostridium [OR = 0.998, 95% CI: (0.9954, 0.9999), p = 0.041], RuminococcaceaeUCG003 [OR = 0.997, 95% CI: (0.9955, 0.9994), p = 0.011], and FamilyXIIIAD3011group [OR = 0.997, 95% CI: (0.9954, 0.9992), p = 0.006] were negatively correlated with the risk of synovitis and tenosynovitis, while two other genera including Ruminococcustorquesgroup [OR = 1.003, 95% CI: (1.0004, 1.0049), p = 0.019] and Parabacteroides [OR = 1.003, 95% CI: (1.0002, 1.0052), p = 0.035] were positively associated with synovitis and tenosynovitis risk. In addition, the data of sensitivity analyses demonstrated that there was no outliers, horizontal pleiotropy, or heterogeneity in the causal relationship of above-mentioned gut microbiota on synovitis and tenosynovitis (p > 0.05). Conclusion: This study results suggested that the gut microbiota was causally involved in synovitis and tenosynovitis, and identified specific bacterial taxa that affect synovitis and tenosynovitis, which provide new insights into the pathogenesis underlying the development of synovitis and tenosynovitis mediated by gut microbiota.